(untitled) (Archaeologia Adriatica, 2022)
In the early 20th century, in the houses of the Grbića Stanovi hamlet in Privlaka near Nin, professor Luka Jelić, PhD, found and documented two fragments of a monument with partially preserved dedication to the imperial numen (Numini Imp. Caesaris Augusti…). Documentation about this valuable find constitutes a part of Jelić’s “Heritage“ kept in the Archaeological Museum in Split. The authors analyze the data recorded by Luka Jelić and observe them in the context of manifestations of honoring the imperial cult in the area of the municipium of Aenona, as well as in the wider area of the Roman Empire.